Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Get quick and reliable solutions to your questions from a community of experienced experts on our platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
[tex]y^2 -6y-66=0\\y1 = \frac{-b+\sqrt{b^2-4ac}}{2a}\\y2 = \frac{-b-\sqrt{b^2-4ac}}{2a}\\= \frac{6+\sqrt{300}}{2}\\= \frac{6-\sqrt{300}}{2}\\[/tex]
[tex]y = 3+5\sqrt{3}\\ y = 3-5\sqrt{3}[/tex]
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.